Gender Inequalities in Academic Achievement among Internally Displaced children in Colombia - Silva-Arias, Adriana Carolina; Sarmiento-Espinel, Jaime Andrés; Gónzalez-Cogollos, Laura Victoria (Revista Latinoamericana de Ciencias Sociales, Niñez y Juventud, 2020)
AbstractUsing 2015 data of the Colombia Demographic and Health Survey, we investigated the incidence of belonging to a household with an Internally Displaced Person (IDP) on the likelihood of grade retention by sex. Particularly, a bivariate logistic regression was used to identify the correlation between families with IDP and children's gender on the probability of repeating a school year. Boys' were negatively affected when they live in an IDP household. Also, boys had a higher likelihood of repeating a grade. We need to know how to act upon the social determinants that create social gaps and disadvantages across IDP, but also, to align with Sustainable Development Goals to eliminate gender inequalities.Keywords: Academic Failure, Grade Repetition, Violence, armed conflicts, gender roles, civil war, Disadvantaged groups, Displaced Persons, War Victims.